The impact of circulation types and their changing thermal properties on the probability of days with snowfall and rainfall in Poland, 1966–2020 - Łupikasza, Ewa B.; Małarzewski, Łukasz; Pham, Quoc B. (Quaestiones Geographicae, 2024)
The frequency of snowfall and rainfall is expected to change due to the warming climate. However, trends in liquid and solid phases are not linearly related to air temperature trends. This paper discusses the impact of thermal properties of circulation types (CTs) on the trends in snowy and rainy days in Poland in the period 1966–2020. The visual observations from 42 synoptic stations, which constitute the most-reliable information on precipitation type, were used to identify the precipitation phase. In most CTs, the air temperature increased between 1966–1985 and 2001–2020, but at various rates depending on the type of circulation. Positive tendencies in the thermal properties of CTs contributed to decreasing trends in winter snowfall and increasing trends in winter rainfall. The rate of tendencies in the probability of the precipitation phases depended on the average temperature and the intensity of warming, in particular CTs. In winter, both the snowfall and rainfall tendencies were the strongest for those CTs with average air temperatures (ATs) close to the freezing point, particularly when the average had crossed that threshold between the years 1966–1985 and 2001–2020. The most rapid tendencies in winter snowfall and rainfall, and in the spring mixed phase were induced by N and NW air advection under cyclonic conditions, bringing air from the rapidly warming Arctic. No trends in the winter mixed precipitation probability resulted from its various tendencies in particular CTs. The probability of snowfall increased during air advection from the southeastern sector, particularly in winter.